Representations of Eve in antiquity and the English Middle Ages - Flood, John (Routledge studies in medieval religion and culture, 2011)
The Bible and its early interpretation -- The influences of non-Christian traditions -- Anglo-Saxon Eve -- Later medieval theology : "she wrecked the whole world" -- Defences of Eve -- Middle English literature -- Epilogue : witches.